Dietary intake pattern in women of reproductive age and its relation to health. - K.C., Gita (2011)
SUMMARY: Women of Reproductive Age in developing countries are one of the most vulnerable populations in the community to malnutrition because of low dietary intake, infection, lack of appropriate health care and inequitable distribution of food within the household. Considering the fact that mother's nutrition directly affects the growth of fetus we can assume that if there is lack of certain nutrients in the diet of mother the new born will also be likely to have severe nutritional deficiencies. In this regard, it becomes relevant to know the dietary pattern of women of reproductive age. Hence, this study is proposed with a view to having a general idea of what women are consuming in their reproductive age and assess whether the prevailing pattern is enough for the age group. This study was done using a cross sectional descriptive methods by taking a sample from women of reproductive age in a selected VDC of Kathmandu district. The main objective of the study was to describe the dietary pattern of women of reproductive age. The major findings of the study are out of the total respondents almost all (95%) were vegetarian with sufficient production of leafy vegetables at home. Also most of them (90%) had enough availability of milk and milk products. Majority of the respondents were found to be consuming food three times a day. It also showed that 56 % of the participants consumed grains thrice a day, followed by 35 % of respondents twice a day. Of the total respondents, 73 % of them were found to consume pulses and legumes twice a day. Similarly, 73 % of the respondents mentioned that they consume green vegetables twice a day and 26% of the respondents mentioned they consume once a day. While looking into the consumption of other vegetables intake it was found that 89 % of them consumed it once a day. Out of the total respondents, 47 % of them mentioned that they consume fruits once a week, while 49 % of them were found to consume milk and milk products 2 -3 times a week followed by 33 % once a week. While looking into the consumption of meat and fish products, 65 % of the respondents were found to consume it 2 - 3 times a week followed by 22 % of them once a week. Almost two third of the respondents mentioned that they took supplements during pregnancy and lactation. However, more than one third failed to take supplements during the period. In conclusion, it was found that the dietary pattern was fairly close to the principle of balanced diet in general. The consumption of supplements was not found to be present in fair number of participants.